The Role of Drawing and Art Classes in The Graphic Design Education - Erengezgin Kafkas, Yasemin (University of Architecture and Urbanism "Ion Mincu", 2014)
This study aims to analyse the role and importance of the Arts relevant courses, concentrating on Drawing lessons, in the light of evolving technology and new expectations in the Graphic Design education era. First, the article briefly focuses on the relationship between art and design area. Then, the topics such as the possible contributions of art and drawing classes in education and the link between art, culture and a good design are covered. In the next section, the old fashioned Graphic Design education methods and new approaches are compared. The relation between creativity and knowledge, necessity of hand drawing while creating designs and the question about the competency of computer design programmes are discussed. The discussion is exemplified through comparison of Graphic Design curriculums from different higher education institutions. Another important question attempted to answer here is, to what extent the computer programmes an instrument of abstract design or the execution process are. The expectations and demands of the students are examined in context of previous discussions. The final objective of the paper is to show that manuel drawing skills and art culture knowledge are still valuable achievements for a graphic design student. Therefore, the work ends with thoughts about convincing them to notice and properly learn these skills.